2001
DOI: 10.1016/s0022-0248(01)00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth of high quality InGaAsN heterostructures and their laser application

Abstract: Focus of this work is the optimization of growth to achieve high quality laser material for emission at 1.3 mm and beyond. GaAs/GaAsN/InGaAsN heterostructures were grown by solid source molecular beam epitaxy. To achieve optimum crystal quality of InGaAsN heterostructures, growth was followed by a high temperature treatment at about 7008C. The high optical quality of our annealed material is attested by large exciton recombination lifetimes (more than 2 ns). Consequently, a decrease of single quantum well tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 7 publications
1
22
0
3
Order By: Relevance
“…This rise in PL intensity is accompanied by an increase in PL wavelength. Xray diffraction on ternary reference samples reveals an increased N-incorporation which has also been reported by other authors [6,7] and is a clear indication that under higher As fluxes the N incorporation is limited by the competition between the group V elements. The same increase in the N content of InGaAsN quantitatively explains the redshift in PL wavelength.…”
Section: Growthsupporting
confidence: 86%
“…This rise in PL intensity is accompanied by an increase in PL wavelength. Xray diffraction on ternary reference samples reveals an increased N-incorporation which has also been reported by other authors [6,7] and is a clear indication that under higher As fluxes the N incorporation is limited by the competition between the group V elements. The same increase in the N content of InGaAsN quantitatively explains the redshift in PL wavelength.…”
Section: Growthsupporting
confidence: 86%
“…There are several reports in the literature, where the N-incorporation mechanisms in dilute nitrides are controversially discussed [37][38][39][40][41][42][43][44][45]. The present paper tries to reconcile this controversy by studying the N-incorporation in great detail by varying the temperature, the V/III-ratio, the V/V-ratio, the growth rate, the reactor pressure, the chemical composition as well as the strain-state of the Ga(NAs) and (GaIn)(NAs) films also for different N-precursor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated 1317-nm emitting InGaAsNGaAsN lasers with improved threshold current density and T 0 compared to GaAs barrier structures [13]. Other reports, using MBE grown material, by Egorov et al also demonstrated improved threshold current, but degraded T 0 values for their single QW InGaAsN-GaAsN lasers [14].…”
Section: Introductionmentioning
confidence: 55%